2002
DOI: 10.1038/ni829
|View full text |Cite
|
Sign up to set email alerts
|

DCs induce CD40-independent immunoglobulin class switching through BLyS and APRIL

Abstract: Immunoglobulin (Ig) class-switch DNA recombination (CSR) is thought to be highly dependent upon engagement of CD40 on B cells by CD40 ligand on T cells. We show here that dendritic cells up-regulate BLyS and APRIL upon exposure to interferon-alpha, interferon-gamma or CD40 ligand. In the presence of interleukin 10 (IL-10) or transforming growth factor-beta, BLyS and APRIL induce CSR from C(mu) to C(gamma) and/or C(alpha) genes in B cells, whereas CSR to C(epsilon) requires IL-4. Secretion of class-switched ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
1,084
3
16

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,149 publications
(1,137 citation statements)
references
References 52 publications
(114 reference statements)
34
1,084
3
16
Order By: Relevance
“…It has been shown that IFN-γ, IFN-α and CD40 ligation stimulate macrophages and DCs to express APRIL and BAFF mRNA (Litinskiy et al, 2002). In addition, we have previously shown that TGF-β1 and IFN-γ stimulate mouse macrophages to express BAFF (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…It has been shown that IFN-γ, IFN-α and CD40 ligation stimulate macrophages and DCs to express APRIL and BAFF mRNA (Litinskiy et al, 2002). In addition, we have previously shown that TGF-β1 and IFN-γ stimulate mouse macrophages to express BAFF (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 82%
“…DCs enhance B cell proliferation and differentiation, (Dubois et al, 1997;. Further, B cell-activating factor (BAFF), which belongs to the TNF family, and a proliferationinducing ligand (APRIL), are expressed by macrophages and DCs, and are critical factors for the growth and survival of both normal and malignant B cells (Fagarasan and Honjo, 2000;Litinskiy et al, 2002). Interestingly, APRIL is known to increase IgA and IgM but not IgG responses to T cell-dependent antigens (Stein et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The production of BAFF by accessory cells may be particularly important to modulate not only B cell survival but also other B cell functions. For instance, engagement of TLR4 by LPS stimulates myeloid DC and macrophages to secrete BAFF, which promotes BCR-and CD40-induced B cell proliferation [10] and favors immunoglobulin class switch recombination [11]. DC can also be triggered to produce BAFF by the TLR2 ligand peptidoglycan [12] and by nucleic acid-containing immune complexes, presumably via TLR9 [13].…”
Section: Introductionmentioning
confidence: 99%
“…APRIL promotes B cell and plasma cell activation and survival and plays important roles in immunoglobulin class switching and antigen presentation (9)(10)(11). BLyS promotes B cell survival and maturation (12)(13)(14)(15).…”
mentioning
confidence: 99%